2013
DOI: 10.2174/13895575113139990008
|View full text |Cite
|
Sign up to set email alerts
|

Potential Efficacy of Some African Plants in Benign Prostatic Hyperplasia and Prostate Cancer

Abstract: Traditional medicine is very popular in Africa and it is considered as an alternative form of health care. Plants and vegetables used in folk and traditional medicine have gained wide acceptance as one of the main sources of prophylactic and chemopreventive drug discovery and this is due to the evidence of particular biological and biochemical characteristics of each plants extracts. The role of these compounds in urological field may be explained by the antiinflammatory effect through interference with prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The burden of BPH on healthcare systems and to society is already high and it is expected to increase in line with the greater life expectancy [4,5]. BPH results from smooth muscle and epithelial proliferation primarily within the prostatic transition zone that can produce LUTS [6-9]. As a consequence, targeting apoptosis may represent a rational therapeutic strategy in the treatment of BPH.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of BPH on healthcare systems and to society is already high and it is expected to increase in line with the greater life expectancy [4,5]. BPH results from smooth muscle and epithelial proliferation primarily within the prostatic transition zone that can produce LUTS [6-9]. As a consequence, targeting apoptosis may represent a rational therapeutic strategy in the treatment of BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate tissue is normally protected from oxidative damage by free radical scavengers and enzymatic antioxidants such as glutathione, catalase, and superoxide dismutase . BPH also involves increased growth of both smooth muscle and epithelial cells mainly in the transition zone of the prostate . Interestingly, Di Silverio et al showed that COX‐II inhibition in human prostatic tissue can produce a significant increase in apoptosis in prostatic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicine which is also called botanical medicine or phytomedicine, refers to the use of plant parts or mixtures of plants extract(s) for medicinal purposes (Russo et al, 2013). Examples of such products includes the leaves and roots of Annona senegalensis, stem of Cissus populnea, the seeds of Garcinia kola, the whole plant of Momordica charantia, the leaves and roots of both Newbouldea laevis and Rauwolfia vomitoria (Russo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%